Studio per due attrici: Adelaide Ristori ed Eleonora Duse - Schino, Mirella (Drammaturgia, 2023)
This essay investigates the relationship between two outstanding actresses, Adelaide Ristori and Eleonora Duse. They are the reference points for two opposing generations, and very different models in terms of art, repertoire choices, leadership. But they are linked by a surprising personal relationship. Dealing with these figures and their relationship also opens a gateway to other issues: the physiognomy of the two generations involved; the change, not only stylistic, between them; the kind of gaze of the older on the younger; women’s issue in theatre. In order to study 19th century theater, we have to take into account the presence of female artists of excellence, women directors, women in charge, women at the top. The situation of women in theatre is highly anomalous, both quantitatively and qualitatively. It is an important phenomenon, which affects all of Europe and Russia, and it is particularly significant in Italy. Within this anomaly the two great women artists choose two diametrically opposed paths: the strength of Ristori is to be in harmony with her times, and this is also confirmed in the management of marriage, declined in the conventional manner whereby the woman relies on and is supported by her spouse. Duse makes very different choices. And with her it becomes more difficult to deal.